ChemInform Abstract: Oxidative Oxygen‐Nucleophilic Bromo‐Cyclization of Alkenyl Carbonyl Compounds Without Organic Wastes Using Alkali Metal Reagents in Green Solvent. Issue 9 (February 2016) - Moriyama, Katsuhiko; Nishinohara, Chihiro; Sugiue, Toru; Togo, Hideo
Abstract: The title reaction proceeds via the oxidative umpolung of bromide using alkali metal bromide and an inorganic oxidant.